Three-dimensional motion corrected free-breathing simultaneous multislice-balanced steady state free precession myocardium perfusion imaging - Naledi Adam; Ronald Mooiweer; Andrew Tyler; Karl Kunze; Radhouene Neji; Peter Speier; Daniel Stäb; John Ng; Shino Kuriakose; Reza Razavi; Muhummad Sohaib Nazir; Amedeo Chiribiri; et al. (Journal of Cardiovascular Magnetic Resonance)
ABSTRACT: Background: To develop a 3D motion-corrected simultaneous multislice-balanced steady state free precession (SMS)-bSSFP acquisition to enable free-breathing myocardial perfusion with high spatial resolution and coverage. Methods: A fast diaphragmatic respiratory navigator (fastNAV) module (<15 ms) was implemented into an SMS-bSSFP sequence for prospective slice-tracking. The remaining 2D in-plane motion was corrected using inline image registration. This approach (SMS-fastNAV) was compared to a reference SMS perfusion with 2D in-plane motion correction only (SMS-Ref) in 10 patients at 1.5T. Each subject underwent both perfusion protocols (six slices, resolution: 1.9×1.9mm2) in a random order. The residual motion of the left ventricule (LV) was assessed by measuring the average DICE coefficient of the LV (avDICE) and the average displacement of the LV center of mass location (avCOM). Subjective assessment of image quality was also performed. Results: SMS-fastNAV led to lower residual LV motion than SMS-Ref before non-rigid image registration as shown by a higher avDICE (0.93±0.02 vs. 0.89±0.04, p<0.002) and decreased avCOM (2.82±0.89 mm vs. 4.23±1.29 mm, p=0.005). After non-rigid image registration, SMS-fastNAV also led to higher avDICE score (0.95±0.01 vs. 0.94±0.02, p<0.027) and tended to decrease avCOM (0.97±0.21 mm vs. 1.01±0.25 mm, p=0.23) with respect to SMS-Ref, suggesting a reduction in through-plane motion. There were no statistical significant differences between both approaches in terms of image quality (SMS-fastNAV: 1.79±0.50 vs. SMS-Ref: 2.00±0.59, p=0.172). Conclusion: A 3D motion correction strategy was successfully developed for free-breathing SMS-bSSFP perfusion with high spatial coverage and resolution and provides improved motion correction with respect to standard in-plane image registration only.